Qualidade da dieta, composição corporal e marcadores bioquímicos do estado nutricional e inflamatório de indivíduos submetidos à cirurgia bariátrica - Braga, Gabriela Bernabé (2023)
Bariatric Surgery (BS) is a procedure for the treatment of severe obesity. The reduction in gastric capacity promoted by BC can affect food intake and compromise the quality of the diet. The Healthy Eating Index (IAS) is a validated tool that allows you to classify diet quality. Objective: To relate the quality of the diet with changes in body composition, biochemical profile of the nutritional and inflammatory status of patients undergoing BS. Methodology: Observational, longitudinal and prospective study, carried out with patients from the Bariatric and Metabolic Surgery Program at the Cassiano Antônio Moraes University Hospital. The research participants were evaluated in three moments from April 2016 to March 2020: before surgery (T0), approximately in the second (T1) and sixth month (T2) after the BS. Anthropometric parameters were evaluated: body mass index, waist circumference, fat mass and fat-free mass; biochemical parameters: total proteins and fractions, transthyretin, C-Reactive Protein (CRP) and Alpha-Acid Glycoprotein (α1-GA). Diet quality was assessed by IAS. Data were analyzed by repeated measures ANOVA or Friedman's test, according to data distribution. For the correlation analysis, the Pearson or Spearman test was used, while for the association analysis, the multiple linear regression analysis test was used, adjusted for sex and age. A significance level of 5% was adopted. Results: The sample consisted of 22 individuals, 81.8% (n=18) female. Individuals had poor diet quality at all times evaluated. BS promoted a reduction in all anthropometric parameters and in serum levels of transthyretin and CRP (p<0.05). There was a negative correlation and association between the IAS and anthropometric parameters and a positive association with transthyretin (p<0.05) at T2. The variation in serum transthyretin concentrations was positively correlated with the variation in IAS and caloric intake (p<0.05). Conclusion: The individuals in the present study had poor diet quality during the period evaluated, which may indicate a concomitant loss of visceral protein mass.